Big Data Trade Survey Pricing, Trading, and Data Protection - Umbu Zogara, Lukas (Scientific Journal of Information System, 2024)
In this era, Big Data is considered as the key to unlocking the growth of people's productivity in daily life. Internet usage, mobile applications and social networks, as well as the internet of things based on smart-grid and so on has an impact on the amount of data collected. The advancement of analytics data provided by machine learning and data mining technology supported by cloud computing, the resulting information will be more useful. Since the advent of Big Data, the dataset has become one type of "new money" in the digital world. Copyright protection mechanisms including digital encryption and watermarking need to be done to maintain data values. To maximize this, an effective container is needed to allow data owners and buyers to trade the data. The focus of the topic is on designing data trading platforms and schemes, supporting effective and efficient data trading, security, and maintaining the privacy of data owners.